Attitude and Knowledge of Belahi Cattle Rearers for Dairy Farming Practices in Shivalik Foothill - Ali, Waris; Garai, Sanchita; Maiti, Sanjit; Lepcha, Chimi Yangzom; Meena, Deepak Chand; Roy, Suman (Indian Journal of Extension Education, 2024)
Belahi cattle are seemed to play an important role in sustaining livelihood security of rural Gujjar pastoralists of the Shivalik foothill of Haryana. So that present study was conducted during June 2019 to March 2021 in selected three districts of Shivalik foothill of Haryana due to native tract of Belahi cattle. From each district one tehsil was selected purposively having the highest Belahi cattle population. Three villages from each Tehsil and twenty migratory Belahi cattle rearer from each village were selected randomly. Therefore, total sample size of the study was 180. Knowledge test and attitude scale developed to ascertain knowledge and attitude of the respondents towards improved dairy farming practices. Belahi cattle rearers possessed medium to higher knowledge and low level of favourable attitude towards scientific dairy farming practices. Majority of the respondents were having good knowledge level about management practices, but very lower level of knowledge about breeding practices.